American night [videorecording (DVD)] - Della Valle, Alessio; Della Valle, Alessio; Rhys-Meyers, Jonathan, 1977-; Cucinotta, Maria Grazia; Hirsch, Emile, 1985- (Lionsgate, 2021)
An art dealer and the head of the New York City mafia fight for money, art, power, and love.